Characterization of dietary fiber from wheat bran (Triticum aestivum L.) and its effect on the digestion of surimi protein. (March 2019) - Lin, Yanan; Chen, Kang; Tu, Dan; Yu, Xina; Dai, Zhiyuan; Shen, Qing
Abstract: Dietary fiber is a class of polysaccharides that can not be digested by the gastrointestinal tract but have a significant physiological role. In this study, the insoluble dietary fiber (IDF) and soluble dietary fiber (SDF) were obtained by enzymatic hydrolysis and lyophilization of wheat bran ( Triticum aestivum L.). The physicochemical properties were to evaluated by laser diffraction, scanning electron microscopy, Fourier-transform infrared spectroscopy and X-ray diffraction. The results showed that the IDF was good at absorbing peanut oil (5.86 g/g), lard (9.63 g/g), cholesterol (4.11 mg/g in small intestine and 2.87 mg/g in stomach), sodium cholate (3.19 mg/g) and nitrite (100% at 105 min), while the SDF showed impressive DPPH, ABTS+ and hydroxyl radical scavenging capacity. Finally, the surimi was fortified with IDF or SDF for in vitro protein digestion assay, and the physiological effects of dietary fiber resulted in a general reduction in digestibility with increased dosages of IDF and SDF. The functional properties of dietary fiber are potentially related with achieving healthy weight, making it a good additive in surimi products industry. Highlights: IDF and SDF were obtained by enzymatic hydrolysis and lyophilization of wheat bran. The physicochemical and functional properties of DF were revealed. IDF is good at absorbing peanut oil, lard, cholesterol, sodium cholate and nitrite. SDF showed impressive DPPH, ABTS.+ and hydroxyl radical scavenging abilities.